Relationship between wool cortisol, wool quality indices of Australian Merino rams and climatic variables in Tasmania - Cobb, Troy; Hantzopoulou, Georgia-Constantina; Narayan, Edward (Frontiers in Animal Science, 2023)
Australia is the world's largest producer and exporter of fine wool. External factors (i.e., nongenetic) that affect wool phenotype need to be identified and managed to minimize any negative effects on wool quality. Climatic stress is one external event that can affect wool phenotype, other stressors include shearing, nutrition, disease, pregnancy, and lambing. This study focuses on the relationship between Saxon Merino ram wool phenotype and wool cortisol.The hypotheses had two parts (i) wool cortisol levels would vary seasonally and variations would correlate with wool phenotype (ii) that these seasonal variations would also correlate with thermal indices. Cortisol levels in Saxon Merino ram wool samples were determined using a cortisol enzyme-immunoassay (EIA) using polyclonal cortisol antibody. The wool cortisol results were correlated for significance with thermal indices including Temperature Humidity Index [THI] and Chill Index [CI] obtained from the Australian Bureau of Meteorology. Part 1 of hypothesis one was supported with wool cortisol showing significant seasonal variation. Part 2 of hypothesis 1 was not supported, with no statistically significant causality present between total wool cortisol levels and the price index of Saxon Merino ram wool. However, there was significant causality between wool cortisol and coarse edge measurement (CEM) of wool.Hypothesis 2, the proposal that thermal indices would impact on wool cortisol was also not supported. It can be concluded that although conclusive causality between total wool cortisol and wool phenotype quality could not be ascertained, there were indirect effects of cortisol levels on wool phenotypes with significant effects on the CEM. The CEM of Merino Saxon ram wool can be manipulated by assessing and managing cortisol levels during the growth cycles of Merino wool, through appropriate nutrition and husbandry procedures stress could be managed.